COREOGRAPHY IN MALAYSIA IN MULTICULTURAL CONCEPT: CASE STUDY PROGRAM MINOR ARTS DANCE UPSI - Nerosti Nerosti (Fakultas Bahasa dan Seni UNP, 2014)
KOREOGRAFI DI MALAYSIA DALAM KONSEP MULTIKULTURAL: KAJIAN KES PROGRAM MINOR SENI TARI UPSIAbstractThis writing is the result of my research entitled “Analisis Deskriptif Koreografi Pelajar Minor Seni Tari UPSI: Kajian Kes Tiga Produksi Tari 2008 – 2011”. The aim of the research is to answer the question: To what extend the dance work by Minor Dance Art students which was presented in Art Dance Production fulfills the coreography elements, by using descriptive analysis method from primary and secondary data. By using qualitative approach which involved library research, observation, interview and by using coreography theory, the research result proves that seventeen Minor Art Dance students’ dance works has been fulfilled the coreography elements. The elements are (a). The choice of theme or idea of work with the early stimulus, that is the stimulation of idea and concept, cinestetic, auditive, and visual. (b). Exploration and improvitation (c). Smoothing and composition. The composition elements has also been described, which include (1). The structure of the work (2). The body movement of the dancer (3). Th floor pattern (4). Music and lighting (5). Costum and make up, lighting. The research also found that eleven of students’ dance works has applied the multicultural concept which has ethnic and classic themes. The multicultural which is viewed as various of uniqueness and the diversity of the cultural ethnic, reflected by each work that is limited by historical context, social, and the origin culture, that includes Melayu ethnic, Minangkabau, Java, Sabah and Serawak, Kelantan, Hindia, and Chinese. Those eleven dances are Andai Randai, San Kipas, Iras, Ngayau, Tatoo Gendup Berpantang, Gawai Batu, Sekar Wangi, Kondattam, Sense of Beauty, Cinta Za’yu dan Jepit.Keywords: Multicultural, Minor Dance, CoreographyAbstrakTulisan ini merupakan hasil penelitian saya yang berjudul